ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT - Sri Trisnaningsih; Saiful Anwar; Muslimin; Fajar Syaiful Akbar (BAJ: Behavioral Accounting Journal, 2020)
This study proposed to analyzing and empirically proving the impact of compliance pressure, task complexity and audit expertise on audit judgment. This study is using quantitative approach method with primary data. The object of this study is using 42 public accounting firms in Surabaya with public accountants as respondents. Sources of data are obtained from answers to questionnaires that have been filled in by 30 public accountants as the study object. The data analysis technique is using multiple linear regression. The findings in this study through the data analysis and hypothesis testing both simultaneously and partially show that compliance pressure, task complexity and audit expertise showing a huge impact on audit judgment. Based on these results, it shows that the variable of task complexity has the most dominant effect on audit judgment.